An Analysis on the Pollution/Contamination of Groundwater and Their Quality: A Review: Assessing the Decline in Groundwater Quality and its Impact (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Groundwater is the foremost source of water for domestic, agricultural and industrial purposes in several countries. Due to human and industrial activities the ground water is contaminated. This is the serious problem now a day. Due to industrial, municipal and agricultural waste containing pesticides, insecticides, fertilizer residues and heavy metals with water groundwater has been polluted by leaching process. The effects of groundwater pollution are wide. In this paper the overview of ground water pollution due to industrial as well as anthropogenic activities. Water quality is affected by both point and non-point sources of pollution. These include sewage discharge, discharge from industries, run-off from agricultural fields and urban run-off. Analysis of the water quality is very important to preserve and prefect the natural eco system. The assessment of the ground water various technologies has been developed and management practices should be carried out periodically to protect the water resources.Groundwater pollution due to anthropogenic activities may impact overall groundwater quality. Organic and inorganic pollutants have been routinely detected at unsafe levels in groundwater rendering this important drinking water resource practically unusable. Vulnerability of groundwater pollution and subsequent impact has been documented in various studies across the globe. Field studies as well as mathematical models have demonstrated increasing levels of pollutants in both shallow and deep aquifer systems. New emerging pollutants such as organic micro-pollutants have also been detected in some industrialized as well as in developing countries. Increased vulnerability coupled with ever growing demand for groundwater may pose a greater threat of pollution due to induced recharge and lack of environmental safeguards to protect groundwater sources.In this review paper, comprehensive assessment of groundwater quality impact due to human activities such as improper management of organic and inorganic waste, and natural sources is documented. A detailed review of published reports and peer reviewed journal papers across the world clearly demonstrate that groundwater quality is declining over time. A proactive approach is needed to prevent human health and ecological consequences due to ingestion of contaminated groundwater.